Electromigration in ULSI interconnections - Tan, Cher Ming 1959- (World Scientific Pub. Co., 2010)
Electromigration in ULSI Interconnections provides a comprehensive description of the electromigration in integrated circuits. It is intended for both beginner and advanced readers on electromigration in ULSI interconnections. It begins with the basic knowledge required for a detailed study on electromigration, and examines the various interconnected systems and their evolution employed in integrated circuit technology. The subsequent chapters provide a detailed description of the physics of electromigration in both Al- and Cu-based interconnections, in the form of theoretical, experimental and numerical modeling studies. The differences in the electromigration of Al- and Cu-based interconnections and the corresponding underlying physical mechanisms for these differences are explained. The test structures, testing methodology, failure analysis methodology and statistical analysis of the test data for the experimental studies on electromigration are presented in a concise and rigorous manner. Methods of numerical modeling for the interconnect electromigration and their applications to the understanding of electromigration physics are described in detail with the aspects of material properties, interconnection design, and interconnect process parameters on the electromigration performances of interconnects in ULSI further elaborated upon. Finally, the extension of the studies to narrow interconnections is introduced, and future challenges on the study of electromigration are outlined and discussed
Keywords: Integrated circuits / Ultra large scale integration; Electrodiffusion